SURVEY OF ATTITUDE TOWARDS BLOOD DONATION AMONG UNDERGRADUATE STUDENTS, SILPAKORN UNIVERSITY, NAKHON PATHOM - Chalongsuk, Rapeepun; Rungruang, Paramat; Boonkhumpong, Kornpat; Lueleerarot, Tirapong; Wattanathaworn, Wongsakorn (Thai Bulletin of Pharmaceutical Sciences, 2017)
จิตสาธารณะเป็นคุณลักษณะที่สำคัญของการมีความรับผิดชอบต่อสังคม การบริจาคโลหิตเป็นกิจกรรมหนึ่งที่แสดงออกถึงการมีจิตสาธารณะของผู้บริจาคโลหิต การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อสำรวจทัศนคติเกี่ยวกับบริจาคโลหิตของนักศึกษาปริญญาตรี มหาวิทยาลัยศิลปากร นครปฐม รูปแบบการศึกษาเป็นการสำรวจเก็บข้อมูลจากนักศึกษาระดับปริญญาตรีจำนวน 426 คน ด้วยแบบสอบถามที่ประกอบด้วย 3 ส่วน คือ ข้อมูลส่วนบุคคล ทัศนคติต่อการบริจาคโลหิตที่วัดด้วย Likert-scale 5 ระดับ และการวัดความรู้ 14 ข้อ ทำการเก็บข้อมูลในช่วงเดือนมกราคม 2556 วิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนา Chi-square test, Relative risk ratio (RR) และ Independent samples test ผลการศึกษาพบว่านักศึกษามีความตระหนักในจิตสาธารณะของการบริจาคโลหิต โดยร้อยละ 97.6 มีทัศนคติที่ดีต่อการสำรองโลหิตไว้เพื่อใช้ในยามฉุกเฉิน ส่วนใหญ่ของกลุ่มที่เคยบริจาคโลหิต (ร้อยละ 88.8) ให้เหตุผลของการบริจาคโลหิต คือ การช่วยเหลือเพื่อนมนุษย์ แต่นักศึกษาร้อยละ 65.5 ไม่เคยบริจาคโลหิต โดยมีเหตุผลว่า พักผ่อนไม่เพียงพอ (ร้อยละ 67.5) และกลัวเข็ม (ร้อยละ 46.3) ตามลำดับ ดังนั้น การจูงใจให้นักศึกษามีความตระหนักในการมีจิตสาธารณะนอกจากการสร้างกิจกรรมเพื่อพัฒนาจิตสาธารณะของนักศึกษาแล้ว จำเป็นที่ต้องมีการให้ความรู้ และการจูงใจผ่านสื่อต่าง ๆ เพื่อขจัดความเชื่อที่ผิด ๆ และสร้างทัศนคติที่ดีต่อกิจกรรมนั้น ๆ ด้วย Public mind is the important attribute for social responsibility. Altruistic blood donation is a activity which represents to public mind manner. The objective of this study was to survey attitude towards blood donation among undergraduate students, Silpakorn University. A cross-sectional survey design was used to collect data from 426 undergraduate students in January, 2016 using the self-administered questionnaire comprising socio-demographic data, attitude about blood donation on a 5 point Likert-scale and knowledge with the 14-item test. For data analysis, descriptive statistics, Chi-square test, Relative risk ratio (RR) and Independent samples test were used. The result showed that the student’s public mind awareness regarding blood donation was high. Most of the respondents (97.6%) had good attitudes about ensuring safe blood supply and guarantee blood reserves. The main reason for blood donation (88.8%) was to save one’s life. But 65.6% had never donated. The main reason of were not getting a good night’s sleep (67.5%) and the fear of the needle (46.3%), respectively. In conclusion, To motivate public mind behaviors of undergraduate students, not only having the activity to participate but also education and motivation through various media is recommended to eliminate misbelieves and to reinforce positive attitudes towards the activities.